Gynecologic Oncology Training Systems in Europe: A Report From the European Network of Young Gynaecological Oncologists. Issue 8 (1st November 2011) - Gultekin, Murat; Dursun, Polat; Vranes, Boris; Laky, Rene; Bossart, Michaela; Grabowski, Jacek P.; Piek, Jurgen M. J.; Manchanda, Ranjit; Grimm, Christoph; Dallaku, Kastriot; Babloyan, Syuzanna; Moisei, Anna; et al.
Abstract : Objective: The objectives of the study were to highlight some of the differences in training systems and opportunities for training in gynecologic oncology across Europe and to draw attention to steps that can be taken to improve training prospects and experiences of European trainees in gynecologic oncology. Methods: The European Network of Young Gynaecological Oncologists national representatives from 34 countries were asked to review and summarize the training system in their countries of origin and fulfill a mini-questionnaire evaluating different aspects of training. We report analysis of outcomes of the mini-questionnaire and subsequent discussion at the European Network of Young Gynaecological Oncologists national representatives Asian Pacific Organization for Cancer Prevention meeting in Istanbul (April 2010). Results: Training fellowships in gynecologic oncology are offered by 18 countries (53%). The median duration of training is 2.5 years (interquartile range, 2.0-3.0 years). Chemotherapy administration is part of training in 70.5% (24/34) countries. Most of the countries (26/34) do not have a dedicated national gynecologic-oncology journal. All trainees reported some or good access to training in advanced laparoscopic surgical techniques, whereas 41% indicated no access, and 59% some access to training opportunities in robotic surgery. European countries were grouped into 3 different categories on the basis of available training opportunities in gynecologic oncology: well-structured, moderately structured, and loosely structured training systems. Conclusions: There is a need for further harmonization and standardization of training programs and structures in gynecologic oncology across Europe. This is of particular relevance for loosely structured countries that lag behind the moderately structured and well-structured ones.